INFLUENCE OF WORK COMPETENCY, WORK DISCIPLINE AND TRAINING ON EMPLOYEE PERFORMANCE AT BANDUNG HOSPITAL - Jayasiddhi; Juan Carlos Sinaga; Hendry (Jurnal Mantik, 2022)
Work competence, work discipline and training are elements that can affect employee performance. This study aims to determine and analyze the effect of work competence, work discipline and training on the performance of consumer employees at Bandung Hospital. This type of research is explanatory research. The total population in this study is the average number of employees per day who make repeated purchases at the company totaling 211 employees. Due to the large number of populations, the sampling technique will be reduced by using the Slovin formula for an error tolerance level of 5% so that there are 138 respondents in the study to which the distribution of questionnaires will be measured using a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that either partially or simultaneously, work competence, work discipline, and training had a positive and significant impact on the performance of consumer employees at Bandung Hospital. Based on the results of this study, the implications for management are to make improvements to work competencies so that they can be better, increase employee work discipline and also add training for all employees in developing their work abilities